2019
DOI: 10.1177/1054773819880291
|View full text |Cite
|
Sign up to set email alerts
|

I Am As Normal As Everyone Now. . . : Examination of Experiences of Patients Undergoing Bariatric Surgery According to Roy’s Adaptation Model: A Qualitative Study

Abstract: The aim of this study is to examine experiences of patients undergoing bariatric surgery according to Roy’s adaptation model (RAM). This is a qualitative study with a phenomenological design. The sample included patients undergoing bariatric surgery ( N: 32). Of all the patients 84.37% were female and 59.38% were married. According to results of the content analysis, adaptive patient behavior was described by the themes “My life has changed”, Everything is beautiful” “I can cope” and “Luckily, I have them” and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 34 publications
3
45
0
1
Order By: Relevance
“…Being overweight can unite or separate the couple (Ledyard & Morrison, 2008), but men feel supported in the struggle to preserve their sexuality (Haga et al., 2020). Coinciding with our results, candidates for bariatric surgery report anxiety and avoidance of romantic or sexual relationships (Pratt et al., 2016), expecting improvements in their frequency, and the comfort and satisfaction they provide after surgery (Kabu & Özbayır, 2019; Steffen et al., 2017). Postbariatric surgery experiences range from improvements in sexual functioning (Steffen et al., 2019) to personality changes (Wallwork, Tremblay, Chi, & Sockalingam, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Being overweight can unite or separate the couple (Ledyard & Morrison, 2008), but men feel supported in the struggle to preserve their sexuality (Haga et al., 2020). Coinciding with our results, candidates for bariatric surgery report anxiety and avoidance of romantic or sexual relationships (Pratt et al., 2016), expecting improvements in their frequency, and the comfort and satisfaction they provide after surgery (Kabu & Özbayır, 2019; Steffen et al., 2017). Postbariatric surgery experiences range from improvements in sexual functioning (Steffen et al., 2019) to personality changes (Wallwork, Tremblay, Chi, & Sockalingam, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Participants told us that MO inhibits their sex life, which worsens with hypogonadism, erection problems, premature ejaculation, advanced age and consumption of antidepressants (Steffen et al., 2017). According to our results, excess skin/fat has negative effects on sexual life (Kabu & Özbayır, 2019; Milhausen, Buchholz, Opperman, & Benson, 2015), and hinders mobility, sexual positions and enjoyment (Wu & Berry, 2018). Some studies show that bariatric surgery can improve erectile function, desire and sexual satisfaction in heterosexual men with MO (Arolfo et al., 2020; Pomares‐Callejón et al, 2018; Xu, Wu, Zhang, & Pei, 2019) although other studies disagree (Carr et al., 2014; Sarwer et al., 2015).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Also, the experience of Turkish pregnant women with nausea and vomiting during pregnancy was assessed using RAM and the participants' experience showed that they were dissatisfied with their relationships with important people in their lives and with supportive resources and disruption of interaction with their social environment [ 25 ]. In another study, the experience of patients who underwent bariatric surgery under the guidance of RAM was examined and the results showed that body image surgery improves social life, personal relationships and performance of participants [ 26 ]. The adaptation experiences of Turkish patients who underwent liver transplant surgery were evaluated according to the RAM.…”
Section: Introductionmentioning
confidence: 99%
“…MO can be prevented with a multidisciplinary approach, including health education, diet, physical exercise and pharmacological treatment [12][13][14]. However, therapies or treatments are not always effective and therefore surgical treatment is required [15]. Bariatric surgery is a reliable method for losing weight in the long term, improving the quality of life, body image and social life of people with MO.…”
Section: Introductionmentioning
confidence: 99%